The Role of Traditional Institutions in Preserving the Lodo Huer Ceremony in Kajowair Village, Riidetut Hamlet, Hewokloang District - Moa, Stevanus; Nuwa, Gisela (Lembaga Riset Mutiara Akbar, 2022)
Traditional institutions as a medium in the process of holding a ceremony, including the traditional Lodo Huer ceremony. In Kajowair Village, hewokloang sub-district, there are traditional institutions that play a role in this process of traditional rituals as referred to as the Lodo Huer custom called Rawin. Traditional institutions (Rawin) have a very important role in the traditional ritual of lodo huer, namely before the traditional ritual ceremony begins, the traditional institution performs a ceremonial ceremony as the opening for the lodo huer ceremony. The traditional institution (moan rawin) as the leader before and after the traditional ceremony take place. The process of the traditional lodo huer ritual in Kajowair Village, Hewokloang sub-district cannot be separated from the role of traditional institutions. Indigenous institutions have a very important position in this regard which relates to common interests in the process of sustaining the traditional ritual of lodo huer, in order to achieve common goals and the welfare of indigenous peoples. Traditional institutions represent indigenous peoples in managing and regulating the implementation of the traditional lodo huer ritual process in Kajowair Village which is believed to be a tradition that is passed down from generation to generation.